Age-Based Trends of Gastric Adenocarcinoma in the United States. Issue 12 (December 2020) - Trumbull, Denslow; Lemini, Riccardo; Elli, Enrique F.; Bagaria, Sanjay P.; Attwood, Kristopher; Gabriel, Emmanuel
Background: Recent studies have shown an increase in the incidence of gastric cancer (GC) among young adults in Asia and Latin America. However, it is unknown if a similar trend is happening in the United States (US). Methods: A retrospective review of the National Cancer Data Base was conducted to identify patients diagnosed with gastric adenocarcinoma between the years of 2004 and 2013. Results: A total of 93 734 patients were included. The 2 age groups below 40 did not see a change in GC incidence; however, age groups above 40 had increasing incidence. Patients aged 18-25 had the largest proportion of stage 4 disease and a poor survival (median 11.5 months), compared to older patients. Conclusion: Despite the increasing trend of GC among individuals, the incidence of GC among young adults is not increasing. However, this subpopulation presents at more advanced stages (clinical stage 4) and thus has worse survival.